Constitutional Principles of Contractual Representation in Ukraine: Problems of Theory and Practice - TSIURA, Vadym; SULEIMANOVA, Susanna; SOTULA, Oleksandr; PANASIUK, Vita; DOBROVOLSKA, Volodymyra (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019DO - 10.14505//jarle.v10.3(41).33, 2019)
The research is devoted to the issue of the nature and essence of the contractual representation as a legal relationship and a constitutional principle.The current understanding of the institution of representation in the context of the provisions of the Code of Civil Procedure of Ukraine and the Civil Code of Ukraine is ambiguous and this problem needs to be solved. In order to determine the true meaning of the legal institute of representation, the authors of the article made an attempt to study it through the lens of the norms of the current constitution of Ukraine.The methods of scientific research, used by the authors are the analysis, the synthesis, the deduction and induction,the comparison-legal method. All these methods in their convergence made it possible to find out the current state of the existing legislation and legal doctrine in the context of contractual representation and to offer the authors’ own vision of directions of improvement of the studied legal institute.In the result of the study the authors made a conclusion that a contractual representation is a kind of representation, arising out of a contract or other act that underlies the will of the person represented (the principal) and the person representing (the attorney) and the agreement between them. It is important for both the practice of law and the theory of law that the understanding of the essence of the said institute and the approaches to regulating relations of representation in the Civil Code and in the Civil Procedure Code be the same.